Learning from religion at a detraditionalizing Catholic university. The case of the required course "Perspectives on religion and meaning" at the Katholieke Universiteit Leuven, Belgium - Annemie Patyn; Joris Geldhof; Annemie Dillen (Acta Theologica)
At the Katholieke Universiteit in Leuven (Belgium), all students are required to follow a course titled “Perspectives on Religion and Meaning”, taught by professors from the Faculty of Theology. This is remarkable since this university, in spite of its history, has a public character to a large extent. In this contribution, the peculiarity of this course is elucidated. Three difficulties with this course, of principal, practical and theological nature, are pointed out. Further, three opportunities of a course like “Perspectives on Religion and Meaning” are considered. To conclude, we draw some lines between these difficulties and opportunities to defend the value of a course like this, even in “pure” public universities.